2017
DOI: 10.1038/s41598-017-01058-y
|View full text |Cite
|
Sign up to set email alerts
|

Network-assisted analysis of GWAS data identifies a functionally-relevant gene module for childhood-onset asthma

Abstract: The number of genetic factors associated with asthma remains limited. To identify new genes with an undetected individual effect but collectively influencing asthma risk, we conducted a network-assisted analysis that integrates outcomes of genome-wide association studies (GWAS) and protein-protein interaction networks. We used two GWAS datasets, each consisting of the results of a meta-analysis of nine childhood-onset asthma GWASs (5,924 and 6,043 subjects, respectively). We developed a novel method to compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Using the network analysis, we also identified APP hitherto not associated with asthma as important hub gene in regulatory network associated with NE tissue. APP gene encoding the amyloid beta precursor protein is known as a major player in Alzheimer's disease (AD) that have immune and inflammatory components ( 32 ). Recent studies also suggested a link between APP and asthma genes ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the network analysis, we also identified APP hitherto not associated with asthma as important hub gene in regulatory network associated with NE tissue. APP gene encoding the amyloid beta precursor protein is known as a major player in Alzheimer's disease (AD) that have immune and inflammatory components ( 32 ). Recent studies also suggested a link between APP and asthma genes ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…APP gene encoding the amyloid beta precursor protein is known as a major player in Alzheimer's disease (AD) that have immune and inflammatory components ( 32 ). Recent studies also suggested a link between APP and asthma genes ( 32 , 33 ). It is revealed that APP was potentially associated with airway hyperresponsiveness through the interaction with a disintegrin and metalloproteinase ( ADAM33 ) ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Network‐based analysis has also been used to amplify marker signals from existing GWAS studies. Liu et al (2017) identified genes that contributed significantly to childhood‐onset asthma by searching for consistent gene modules between two large GWAS datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of prior studies have integrated GWAS data with networks [16][17][18][19][20][21][22], the majority of these studies tended to focus on single diseases or phenotypes [23][24][25][26]. The potential for improved insights by integrating GWAS data with protein-protein interaction networks in particular, comes from the finding, that the protein products of genes within GWAS loci physically interact with each other more than expected by chance [27].…”
Section: Introductionmentioning
confidence: 99%